Regional structures and mobility dispositions: A multilevel proportional- & partial-proportional odds approach - Christoph Kern (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
In the light of persistent regional disparities in Germany, a wide range of studies discuss the role of regional characteristics in explaining the mobility behavior of individuals. Although multi-stage mobility theories underline the importance of regional structures particularly within the first stage of the decision-making process - whereas the actual mobility behavior is often seen as being dependent on intervening factors and restrictions - only few studies consider contextual characteristics while modeling mobility intentions or dispositions. Above all the potentially varying subjective evaluation of local opportunity structures of different groups of actors is rarely taken into account in previous empirical investigations. In order to close this gap, the present study models mobility dispositions as a function of individual as well as regional covariates and also includes interactions between these two levels. With this approach, some light can be shed on the underlying mechanisms concerning regional structures in the decision-making process. The empirical findings show considerable main and interaction effects regarding the local labor market situation and, to a somewhat lesser extent, concerning the development of the regional economic climate. Formally, the empirical models are implemented using a multilevel proportional- as well as partial-proportional odds approach, whereby it is possible to relax the restrictive assumption of equal effects of the covariates at every stage of the ordered outcome variable. The incorporation of small scale structural features is enabled by the usage of SOEP-Geodata.
Keywords: 330